PEMENUHAN HAK ANAK DAN KESEHATAN DALAM PROSES PEMIDANAAN: TINJAUAN YURIDIS PENERAPAN DIVERSI DAN KEADILAN RESTORATIF DI INDONESIA - admin JICLS; Dita Rosalia Arini; Yuliana Yuli Wahyuningsih; Satino; Uta Provinsiana Sukmara (Jurnal Yuridis, 2026)
Children who come into contact with the law require special protection to ensure the fulfillment of their human rights, including the rights to health, education, and development. This study discusses the regulation of children's rights fulfillment in the criminal justice process through mechanisms of diversion and restorative justice based on the Indonesian legal system, as well as analyzes whether their implementation has been able to optimally realize children's rights. The research uses a normative legal method with a statutory and conceptual approach through literature review. The results show that Law Number 11 of 2012 has regulated diversion and restorative justice as forms of child protection. However, its implementation has not been optimal due to resource limitations, differing understandings among law enforcement officials, and minimal institutional support. Strengthening the implementation is necessary so that children's rights protection can be effectively realized.